(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the educational opportunities of persons with special educational needs, factors of improving pedagogical conditions, the causes of problems that may arise in connection with the improvement of their educational services. The conditions created for students with special educational needs and their activity in educational processes are investigated, scientific conclusions are given.